Pengaruh metode akupuntur terhadap penurunan kekeringan dan kemerahan kulit pada pasien xerosis - Raafika Studiviani Dwi Binuko; Flora Ramona Sigit Prakoeswa (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Xerosis, or dehydrated skin, significantly impacts comfort. Severely dry skin can cause severe itching, irritation, and physical discomfort. It can disrupt sleep, concentration, and daily performance of individuals. Although several studies have evaluated the impact of acupuncture on skin health, strong scientific evidence regarding its effectiveness in treating xerosis is still limited.Objectives: This study aimed to evaluate the influence of acupuncture on reducing skin dryness and redness in patients with xerosis.Methods: This research collected data from 30 patients with xerosis who underwent acupuncture sessions. Skin dryness and redness scores were measured before and after the acupuncture session. The collected data were then analyzed using descriptive statistics and paired samples t-tests.Results: The results of the study showed that acupuncture significantly influenced reducing skin dryness scores by 7,36% and skin redness scores by 15,2% in patients with xerosis after the acupuncture session. This indicates that acupuncture effectively addresses the symptoms of xerosis by reducing skin dryness and redness. This research provides evidence supporting the use of acupuncture as an effective alternative therapy in managing xerosis and improving the quality of life for patients.Conclusion: In this study, acupuncture has been proven to reduce skin dryness and redness in patients with xerosis significantly. These findings suggest that acupuncture can be an effective therapeutic option in addressing the symptoms of xerosis, such as skin dryness and redness. The use of acupuncture as a non-invasive and safe alternative therapy can enhance the quality of life for patients experiencing xerosis.